Tax Audits as Scarecrows. Evidence from a Large-Scale Field Experiment - Marcelo Bergolo; Rodrigo Ceni; Guillermo Cruces; Matias Giaccobasso; Ricardo Perez-Truglia (Institute of Labor Economics (IZA), 2019)
The canonical model of Allingham and Sandmo (1972) predicts that firms evade taxes by optimally trading off between the costs and benefits of evasion. However, there is no direct evidence that firms react to audits in this way. We conducted a large-scale field experiment in collaboration with Uruguay's tax authority to address this question. We sent letters to 20,440 small- and medium-sized firms that collectively paid more than 200 million dollars in taxes per year. Our letters provided exogenous yet nondeceptive signals about key inputs for their evasion decisions, such as audit probabilities and penalty rates. We measured the effect of these signals on their subsequent perceptions about the auditing process, based on survey data, as well as on the actual taxes paid, based on administrative data. We find that providing information about audits had a significant effect on tax compliance but in a manner that was inconsistent with Allingham and Sandmo (1972). Our findings are consistent with an alternative model, risk-as-feelings, in which messages about audits generate fear and induce probability neglect. According to this model, audits may deter tax evasion in the same way that scarecrows frighten off birds.
Keywords: C93; H26; K34; K42; Z13; 330; tax; evasion; audits; penalties; frictions